Landscape, boundaries, and the limits of representation: The Stolpersteine as a commemorative space - Volmert, Miriam (Nordisk judaistik/Scandinavian Jewish Studies, 2017)
The article discusses the commemorative concept of Gunter Demnig’s ongoing art project Stolpersteine, which is considered one of the world’s largest decentralised Holocaust memorials. Stolpersteine are small, cobblestone-size memorial stones in urban spaces which are dedicated to individual victims of Nazism; it is the project’s aim to install the stones in the pavement in front of an individual’s last-known place of residence. The article aims to analyse the commemorative facets of the project’s spatial dimension in relation to the concept of the ‘residential’. The value of dwelling, presented in Demnig’s project as a common ground for the commemoration of all victims as individual citizens, forms a predominant component in public reception. It contributes to a synthesising perception of each stone as being part of a vast commemorative landscape. This landscape, however, is semantically marked by an immanent concept of border, which suggests a polarising separation between included civil spaces and excluded heterotopias. By deviating from the project’s general principles of placement and inscription, certain individual stones render visible this implicit borderline, thereby also critically reflecting on concepts of ‘inside’ and ‘outside’.